Use of epitope libraries to identify exon-specific monoclonal antibodies for characterization of altered dystrophins in muscular dystrophy. - Nguyen, T M (1993)
The majority of mutations in Xp21-linked muscular dystrophy (MD) can be identified by PCR or Southern blotting, as deletions or duplications of groups of exons in the dystrophin gene, but it is not always possible to predict how much altered dystrophin, if any, will be produced. Use of exon-specific monoclonal antibodies (mAbs) on muscle biopsies from MD patients can, in principle, provide information on both the amount of altered dystrophin produced and, when dystrophin is present, the nature of the genetic deletion or point mutation. For this purpose, mAbs which recognize regions of dystrophin encoded by known exons and whose binding is unaffected by the absence of adjacent exons are required. To map mAbs to specific exons, random "libraries" of expressed dystrophin fragments were created by cloning DNAseI digestion fragments of a 4.3-kb dystrophin cDNA into a pTEX expression vector. The libraries were then used to locate the epitopes recognized by 48 mAbs to fragments of 25-60 amino acids within the 1,434-amino-acid dystrophin fragment used to produce the antibodies. This is sufficiently detailed to allow further refinement by using synthetic peptides and, in many cases, to identify the exon in the DMD (Duchenne MD) gene which encodes the epitope. To illustrate their use in dystrophin analysis, a Duchenne patient with a frameshift deletion of exons 42 and 43 makes a truncated dystrophin encoded by exons 1-41, and we now show that this can be detected in the sarcolemma by mAbs up to and including those specific for exon 41 epitopes but not by mAbs specific for exon 43 or later epitopes.